Effects of NPK source on the dry matter partitioning in cool season C3-cereals (wheat, rye, barley, and oats) at various growth stages. (7th February 2017) - Amanullah,
ABSTRACT: Dry matter (DM) partitioning into root, leaf, stem, shoot dry weight plant −1 response in four cool season C3 -cereals viz. wheat ( Triticum aestivum L.), rye ( Secale cereale L.), barley ( Hordeum vulgare L.) and oats ( Avena sativa L.) was investigated at 30, 60 and 90 days after emergence (DAE) under eight nitrogen, phosphorus and potassium (NPK) sources: S1 = 20-20-20, S2 = 20-27-5, S3 = 7-22-8, S4 = 10-10-10-20S, S5 = 11-15-11, S6 = 31-11-11, S7 = 24-8-16, and S8 = 19-6-12 in pot experiment at Dryland Agriculture Institute, West Texas A&M University, Canyon, Texas, USA during winter 2009-10. A considerable variation in DM partitioning into various plant parts was observed in the four crop species at different growth stages and NPK source. At 30 DAE, 27% of the total DM per plant (TDMPP) was partitioned into roots and 73% into shoots (19% stems + 54% leaf). Only16 % of the TDMPP was partitioned into roots and 84% into shoots (18 % stem + 66 % leaf) at 60 DAE. At 90 DAE, 29% of TDMPP was partitioned into roots and 71 % into shoots (33 % stems + 38 % leaf) at 90 DAE. Percent DM partitioning into stems ranked first (33%) at 90 DAE > at 30 DAE (19%) > at 60 DAE (18 %). With advancement in crops age, DM partitioning into various crop parts increased. The root DM plant −1 (RDMPP) increased from 11.5–722 mg plant −1 ; stem DM plant −1 (STDMPP) from 8.3–889.0 mg plant −1 ; leaf DM plant −1 (LDMPP) from 23.1–1031.0 mg plant −1 ; shoot DM plant −1 (SHDMPP) from 31.3–1921 mg plant −1, and TDMPP increased from 42.9–2693.0 mg plant −1 at 30 and 90 DAE, respectively. Because of the higher N contents in S7 (24:8:16) and S6 (31:11:11) reduced the DM partitioning into various plants parts as well as TDMPP at all three growth stages. The adverse effects of S6 and S7 on DM partitioning was more on oats > rye > wheat > barley. The S4 with 10:10:10 (NPK) and :20S was not toxic at 30 DAE, but at 60 and 90 DAE it became toxic that adversely affected the DM partitioning as well as TDMPP probably may be due its high sulfur (20%) content which lacking in other NPK sources. The DM partitioning to various parts of barley and wheat was more than oats and rye at different growth stages (barley > wheat > rye > oats). Since the DM portioning values were determined on the average of five plants in pot experiment under organic soil at field capacity; in case of field experiments more research is needed on various crop species/varieties under different environmental conditions particularly under moisture stress condition.